Early and Intermediate Hospital-to-Home Transition Outcomes of Older Adults Diagnosed With Diabetes. (February 2016) - LaManna, Jacqueline B.; Bushy, Angeline; Norris, Anne E.; Chase, Susan K.
Purpose: The purpose of this study was to identify factors affecting early and intermediate hospital-to home transition outcomes of older adults with preexisting diabetes mellitus. Methods: A mixed-methods design was used. A sample of 96 hospitalized older adults with a prior diagnosis of diabetes were recruited within 4 hours of discharge. Data reflective of general health status, diabetes status, perceived discharge readiness (Readiness for Hospital Discharge Scale), hospitalization, and anticipated postdischarge support were gathered upon enrollment. Transition outcome data including unplanned care encounter occurrences, perceived transition quality (Care Transition Measure-15), and postdischarge difficulty (scale and free responses to the Post-Discharge Coping Difficulty Scale [PDCDS]) were obtained by telephone interview 7 and 30 days after discharge. Three unique, dichotomous variables were created from recurrent subthemes that emerged during content analysis of free-response data and were used in statistical testing. Binary logistic regression was performed to identify predictive factors for an unplanned care encounter within 30 days of discharge. Results: Multimorbidity was prevalent in participants. Difficulties managing medications, blood glucose, and chronic illnesses other than diabetes were common problems. Higher PDCDS scores 7 and 30 days following discharge and difficulty managing a nondiabetes chronic health problem were predictive of an unplanned care encounter within 30 days of discharge. Conclusions: Multimorbidity complicates home recovery of older adults with diabetes. Diabetes adds complexity to hospital-to-home care transitions. Transition difficulties predict higher risk for an unplanned care encounter. More intensive follow-up of older adults with diabetes during the first month following discharge is recommended.